Dental Practices during COVID-19 Pandemic: A Guide for Dental Health Professionals - Nauman Rauf Khan (BioMedica, 2020)
Worldwide, health, medical and dental professionals are at the front line of the COVID-19 outbreak and playing at hands with the hazards that put their lives at stake of getting infected. Hazards include pathogen exposure, long working hours, psychological distress, fatigue, occupational burnout, stigma, and physical and psychological violence. Four specialties are further declared as highly susceptible to contamination with COVID-19 virus which include ENT, Ophthalmology, Dermatology and Dentistry that government was forced to stop their OPDs country wise. Dental practices are those hospital areas that are potentially affected with COVID-19, strict and effective infection control protocols are urgently needed, for this FDI World Dental Federation (FDI) played its role and brought few SOPs for the dental practice which are highlighted in this article. The aim of this manuscript is to help update information among dentist and lead them towards safer dental practice.